Male Homoerotic Practices in Achaemenid Persia: An Overview - Treuk Medeiros de Araujo, Matheus (Revista Archai, 2024)
Descriptions of Ancient Persian male homoeroticism come mainly from Classical sources, which, however, seem to present divergent testimonies regarding this practice. Some authors apparently provide proof for its widespread acceptance, whereas others, particularly later authors, emphasized its prohibition. Considering the many difficulties involved in the reconstruction of Persian history through the eyes of classical Greeks and Romans, this article aims to provide a brief overview of the subject, with some clues to the question of the origin, form, and tolerance of same-sex love in Achaemenid Persia. We agree that homoerotic practices were attested and likely accepted at some level in Achaemenid Persia. However, we believe that the evidence available to us is not enough to obtain a full understanding of this phenomenon. It is also stressed that not every Greek or Roman reference to Persian male homoeroticism should be taken at face value, as some are distorted and fictitious or lack firsthand knowledge. Finally, we briefly address the image of eunuchs as sexual partners of Achaemenid kings.